Charles, the Prince of Wales at the Court of Philip IV of Spain: the «Incognito» Trip and the Problem of Exchanging Gifts - P. Yu. Kosheleva (Vestnik MGIMO-Universiteta)
The article studies the tradition of exchanging gifts during diplomatic negotiations for marriage using a historical reconstruction of the trip of the English Prince Charles Stuart to Madrid in 1623 to negotiate his marriage with the Spanish Infanta Maria as a crucial case. The heir to the English throne personally arrived in Madrid «incognito» to speed up the negotiations. These circumstances created problems for the Spanish side because the reception ceremony was not developed for such a case. Besides, the «incognito» trip complicated the question of exchanging gifts. Later, such trips of monarchs would become a common practice. However, this case was one of the first precedents which forced the existing ceremonial procedure of gift exchange to undergo modifications. The article focuses on functions of exchanging gifts during marriage negotiations and studies the effects of an «incognito» trip on the course of the negotiations.The research is based on the letters of king James and his son Charles and eyewitness reports from the English and Spanish sides. The article claims that Prince Charles’ trip «incognito» changed the traditional procedure of exchanging gifts: the exchange happened before the prince’s departure and was initiated by the Spanish side. Nevertheless, this ritual has not lost its symbolism and significance in the rhetoric of negotiations. Gifts were used as a means of communication, an indicator of the influence of states and the way of their self-presentation.